Queer Zines in Madrid in the 1990's - Lopez Casado, Laura (2022)
The aim of this paper is the study of queer zines produced in Madrid in the 1990’s. There were two pioneer groups in queer activism in Spain, La Radical Gai formed by gay men and LSD, formed by lesbians. La radical Gai published six numbers of their zine De un plumazo, plus two dossiers (one about HIV and the other one about a homophobic attack). LSD was created one year later than La Radical Gai; they published four numbers of Non-Grata. Both groups share ideology, but had different aims and agenda because of their specific gender experience: the main theme for gay men was HIV, whereas lesbians mainly focused on visibility. Albeit the groups did not denominate themselves as queer when they were formed (1991 La Radical Gai, 1993 LSD), they were the first to coin this term in the Spanish context (Solá, 2012, p. 267). La Radical Gai named their zine Queerzine in 1993 and LSD use this term in their first zine published in 1994, where they already defined themselves as queer lesbians. This paper will analyze these zines as historical documents, which help us to understand the characteristics and history of the zine production in Spain; as well as, the introduction of Queer Theory in the context of Madrid in the 1990›s. The zines were not only important for the academic group of Queer Theory but also for the activism movement of that period. Produced by university students, some of which continued their careers in academia, these zines promoted and boasted the introduction of Queer Theory in the University.